Penerapan Konsep Neo-Vernakular pada Desain Atap Amorty Billiards Indonesia di Kota Malang - Cahyaningrum, Eka; Anggraini, Rheina; Murti, Farida; Tohar, Ibrahim (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
This study explores the application of neo-vernacular architectural concepts to the roof design of the Amorty Billiards Indonesia building in Malang City. Neo-vernacular architecture is included in an approach that blends traditional local characters with modernity, using local materials and culture. The research method used in this study is a qualitative method through direct observation and documentation. The results of this research show that building roofs using clay tiles provide coolness and weather resistance even though they require regular maintenance. The Joglo Lawakan roof shape was chosen to add aesthetic and symbolic value to Javanese culture. This combination creates a classic and modern impression, enriches the aesthetics of the building and supports the preservation of local cultural values. This research concludes that the Implementation of Neo-vernacular architecture on the Amorty Billard roof has a positive impact on the environment and maintains traditional values ​​in a modern architectural context.